Numerical Analysis of Submarine Hydrodynamic Force Near the Seabed - Muhamad Ridwan Utina; Rina Rina; Endah Suwarni; Putri Virliani; widodo widodo; Dian Purnama Sari (Department of Naval Architecture - Diponegoro University, 2023)
One of the aspects that need to be considered in designing a submarine is the effect of the hydrodynamic aspect on resistance and maneuverability in various operating conditions. In certain conditions, submarines operate in conditions near the seabed. In general, submarines are designed to operate in submerge and surface mode. However, under certain conditions, submarines need to operate near the surface of the seabed. Only a few papers or journals have discussed the hydrodynamic aspects of submarines in their operating mode near the seabed. Several methods such as numerical and physical modeling tests can be used to predict the hydrodynamic capabilities of a submarine. This paper discusses the effect of the hydrodynamic aspects that occur in submarines when operating near the sea bed using the numerical CFD method. This method has high flexibility compared to experimental methods and does not require a long time to get the results. In this simulation, a submarine model with a length of 2 m is used.